Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Pantai Sine Tulungagung - Nurnizam, Galuh; Hastuti, Maria Agatha Sri Widyanti (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Indonesia is an agrarian country that has many advantages that can be used as a resource in increasing economic growth. One of them is a tourism place. This study was conducted to find out the existence of: 1) the influence of facilities on visitor satisfaction. 2) the effect of service quality on visitor satisfaction. This study uses a type of quantitative research. The population is 96 visitors to Sine Tulungagung Beach using saturated sampling techniques. The method used is the questionnaire (questionnaire) method. The results of this study show that: 1. Partially the value of t-calculated > ttable is 2.365 > 1.987 and the sig. value is 0.020 < 0.05, namely there is a positive and sig. effect between facilities on visitor satisfaction. 2. Partially, the value of t-calculated > ttable is 7.768 > 1.987 and the sig. value is 0.000 <0.05, which has a positive and sig. effect between the quality of service on visitor satisfaction. Simultaneously the value of Fcal > Ftable (155.747 > 3.942) and the sig. value are 0.000 < 0.05. Adjust R Square by 0.765 or equivalent to 76.5%. This shows that 76.5% of changes in visitor satisfaction (Y) are influenced by amenities (X1) and service quality (X2). The remaining 23.5% of the change in visitor satisfaction was influenced by other factors other than the variables of facilities and service quality.